A teoria democrática e a participação popular : as trajetórias participativas no Recife e em Módena - Scavo, Davide Giacobbo (2010)
This work basically achieve three goals. Critically investigate the liberal democratic regime and its historical reformulation, rejecting the popular power and popular self-organization, limiting the entry of normal citizen in decision-making, believing in the market as a mediating body in regulating of the different life spheres of social. Starting from the critical liberal democracy, it discussed the concept of popular participation in the democracy, searching new democratically horizons, where the masses could have the opportunity to make decisions about their own destiny. On the basis of theoretical discussion on participation, we discuss a concrete instrument of participation, the Participatory Budgeting, comparing two participatory experiences in North and South